Biochemical mechanisms preventing wilting under grafting: a case study on pumpkin rootstock grafting to wax gourd - Fu, Houlong; Fu, Junyu; Zhou, Bin; Wu, Haolong; Liao, Daolong; Liu, Zifan (Frontiers in Plant Science, 2024)
Wax gourd wilt is a devastating fungal disease caused by a specialized form of Fusarium oxysporum Schl. f. sp. benincasae (FOB), which severely restricts the development of the wax gourd industry. Resistant rootstock pumpkin grafting is often used to prevent and control wax gourd wilt. The “Haizhan 1” pumpkin has the characteristic of high resistance to wilt, but the mechanism through which grafted pumpkin rootstock plants acquire resistance to wax gourd wilt is still poorly understood. In this study, grafted wax gourd (GW) and self-grafted wax gourd (SW) were cultured at three concentrations [2.8 × 106 Colony Forming Units (CFU)·g−1, 8.0 × 105 CFU·g−1, and 4.0 × 105 CFU·g−1, expressed by H, M, and L]. Three culture times (6 dpi, 10 dpi, and 13 dpi) were used to observe the incidence of wilt disease in the wax gourd and the number of F. oxysporum spores in different parts of the soil and plants. Moreover, the physiological indices of the roots of plants at 5 dpi, 9 dpi, and 12 dpi in soil supplemented with M (8.0 × 105 CFU·g−1) were determined. No wilt symptoms in GW. Wilt symptoms in SW were exacerbated by the amount of FOB in the inoculated soil and culture time. At any culture time, the amount of FOB in the GW soil under the three treatments was greater than that in the roots. However, for the SW treatments, at 10 dpi and 13 dpi, the amount of FOB in the soil was lower than that in the roots. The total phenol (TP) and lignin (LIG) contents and polyphenol oxidase (PPO) and chitinase (CHI) activities were significantly increased in the GWM roots. The activities of phenylalanine ammonia lyase (PAL) and peroxidase (POD) initially decreased but then increased in the GWM roots. When the TP content decreased significantly, the LIG content and PAL and CHI activities increased initially but then decreased, whereas the PPO and POD activities did not change significantly in the SWM roots. The results indicated that the roots of the “Haizhan 1” pumpkin stock plants initiated a self-defense response after being infected with FOB, and the activities of PPO, POD, PAL, and CHI increased, and additional LIG and TP accumulated, which could effectively prevent FOB infection.